MODERN TECHNOLOGIES OF MARKETING INTELLIGENCE (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The purpose of the article is to explore the use of the latest technologies in marketing intelligence, and to offer a vision of its use without harming the social and physical health of consumers. The methodological basis of the research was foreign and domestic publications and analytical reviews on the problems of marketing intelligence using web analytics. The proposed approaches can be taken into account by the marketing services of domestic enterprises when conducting marketing intelligence. An example of Google Analytics examines the technology of marketing intelligence. It is concluded that the beginning of development of open methods of processing private data of users without their direct identification is positive. which would limit the interference with the privacy of people, leaving marketing intelligence possible, and would prevent its negative impact on people's lives.
Keywords: marketing intelligence, site, Google Analytics, web analytics system, audience